The Principles of Examination of Patients with Detected Melanoma Suspected Skin Neoplasm in the Primary Health Care Stage - V. N. Larina; T. A. Gaydina; A. S. Dvornikov; K. E. Nazimkin (Архивъ внутренней медицины, 2022)
Currently, in the structure of mortality in the Russian Federation and a number of other countries, oncological diseases occupy a leading position among other causes. Melanoma of the skin is one of the most aggressive malignant tumors, with rapid progression, often leading to death in a fairly short time. Early detection and rationally organized refferral of patients with diagnosed skin melanoma in primary health care settings is aimed at reducing morbidity and mortality from malignant diseases, and improving the quality of life of patients. Research results suggest that the increased incidence of skin melanoma is due to both overdiagnosis. and an increase in the alertness of doctors and the population in relation to pigmented skin formations. The article discusses the proven risk factors for the development of skin melanoma, since this disease is potentially reversible. Attention is paid to modern clinical methods for predicting the course of skin melanoma. The review article examines computer-based methods for screening and diagnosing skin melanoma, applicable in primary health care settings. A separate section is devoted to dermatoscopy or epiluminescence microscopy, which refers to the study of pigmented skin lesions using surface microscopy. A list of studies is presented in case of suspicion of a malignant neoplasm of the skin / melanoma of the skin in a patient who sought medical help at a medical and prophylactic institution. The significance of the criteria of the ABCDE algorithm, the “Argenziano” algorithm in the study of pigmented skin lesions with further analysis of the results by artificial intelligence for decision-making is discussed.